Transcripts, genes and bands in 315,000 base-pairs of Drosophila DNA. - Hall, L.M.C.; Mason, P.J.; Spierer, P. (Journal of Molecular Biology, 1983)
We have mapped transcripts arising from 315,000 base-pairs of DNA from chromosome region 87D,E of Drosophila melanogaster. The DNA is represented in a series of overlapping recombinant phages; it constitutes about 14 bands in the polytene chromosome from 87D5,6 to 87E5,6 and contains the essential sequences for at least 12 complementation groups. We have defined 20 discrete polyadenylated RNA species transcribed from non-repetitive DNA in the region at various developmental stages. There is a generally good correlation between the position of transcription units, chromomeric units and complementation groups but with some significant exceptions. In particular, the two large bands in the region (E1,2 and E5,6) each contain several transcription units. We also find that a major part of a large band (E1,2) has no detectable transcripts and is apparently genetically silent.